IDENTIFIKASI TIGA ISOLAT CENDAWAN PENGHASIL GAHARU DARI NUSA TENGGARA BARAT DENGAN MENGGUNAKAN PRIMER ITS DAN TEF 1-α - Y.M.M Anita Nugraheni; Lutfi Anggadhania; Riza Arief Putranto (Jurnal Pemuliaan Tanaman Hutan, 2015)
Several isolates of agarwood-forming fungus in Gyrinops versteegii have been isolated from the result of exploration in Lombok and Sumbawa Islands. This study aimed to identify the three fungus associated with the agarwood formation in G. versteegii originated from Lombok Tengah, Alas, and Lombok Barat, Nusa Tenggara Barat. The three fungus cultured in liquid medium PDB (Potato Dextrose Broth) and incubated for 1 month in shaken culture. The mycelium of each fungus was harvested for DNA isolation. Amplification is done by Polymerase Chain Reaction (PCR) using the Primers ITS and TEF with obtained amplicon having base length ranging of 300-600 bs. BLAST analysis showed that the three fungus have similarity with Fusarium solani. These results were confirmed by phylogenetic tree where all fungus has genetic relationship with F. solani.